Good governance pengelolaan sampah: komitmen negara terhadap lingkungan hidup - Niken Wahyuning Retno Mumpuni; Mustika Prabaningrum Kusumawati (Jurnal Cakrawala Hukum, 2021)
Indonesia already has rules that govern this, and the implementation of environmental management policies in accordance with the principles of good governance. Policies will not be effective when policymakers make mistakes in formulating problems. Therefore, it is necessary to study the problem of waste and how the implementation of the principles of good governance in creating disposable waste and plastic management policies. Through a juridical-normative approach this research will describe and analyze the problem in accordance with the provisions of the applicable laws and regulations. Besides that, it is added with legal materials such as literature study from literature books, papers, articles, journals, research results and other scientific works related to this research. The problem map is the category of rubbish that is difficult to manage, one of which is plastic waste where the form of plastic waste is in the form of packaging, then disposable items, microbeads, straws, ear cleaning, plastic bags, polystyrene and flexible plastic. The importance of community participation in waste management in the scope of central and regional governments, as well as the community also has the right to make suggestions and provide advice related to waste problems. The form of efforts to ensure the security of everyone and society and to advance economic, social and other fields in accordance with the will of the people is the concept of good governance.How to cite item: Mumpuni, N. W. R., Kusumawati, M. P. (2021). Good governance pengelolaan sampah: komitmen negara terhadap lingkungan hidup. Jurnal Cakrawala Hukum, 12(1),79-89. doi:10.26905/idjch.v12i1.5725.